Solvent-dependent photoluminescence emission and colloidal stability of carbon quantum dots from watermelon peels - Zaini, Muhammad Safwan; Liew, Josephine Ying Chyi; Paiman, Suriati; Tee, Tan Sin; Kamarudin, Mazliana Ahmad (Springer New York, 2023)
Waste peels are considered an environmental burden and typically disposed in landfills. The aim of this study was to investigate the effects of various solvents on the luminescence properties of carbon quantum dots (CQDs). Watermelon peels were recycled and reuse as precursors for the synthesis of biomass CQDs via a green carbonization method. The colloidal stability, surface charge, and particle size were characterized using zeta potential and dynamic light scattering (DLS). DLS revealed that the size of the CQDs was approximately 5.80 ± 0.4 nm to 9.74 ± 0.8 nm. The high-resolution transmission electron microscopy (HRTEM) results demonstrated a correlation with the DLS results. The optical properties were characterized by photoluminescence (PL) and UV-Visible (UV-Vis) spectroscopy. PL measurements at different excitation wavelengths revealed that the CQDs emissions were influenced by the polarity of the solvents. Meanwhile, the Fourier transform infra-red (FTIR) results showed the presence of oxygen-containing groups on the surface of the CQDs. These results deepen our understanding of the solvent-dependent behavior and colloidal stability of the CQDs